Preparation method of antistatic carpet

By doping polyacrylonitrile with 1-hydroxypyrrole with polypyrrole and crosslinking agent, conductive fibers are prepared and spun into yarn with modified polyacrylonitrile fibers, the problem of poor effect of existing anti-static carpets in dry environments is solved, and the effects of efficient anti-static, washing and friction color fastness are achieved.

CN119900124APending Publication Date: 2025-04-29山东立伟地毯有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411967737.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing anti-static carpets have poor effect in dry environments, poor color fastness, poor flexibility, and poor washing resistance, which affect the appearance and service life of the carpet.

Method used

Conductive fibers are prepared by doping polyacrylonitrile with 1-hydroxypyrrole with polypyrrole and crosslinking agent, and spinning them into yarn with modified polyacrylonitrile fibers, and an anti-static carpet is made by wet spinning process.

Benefits of technology

It has achieved efficient anti-static properties of anti-static carpets, significantly improved washing resistance and friction color fastness, and has an elongation of break of 57-60%, which meets the anti-static requirements of carpets in general places.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a preparation method of an antistatic carpet, and belongs to the field of carpets.The preparation method comprises the steps of preparing modified polyacrylonitrile, preparing 1-hydroxyl pyrrole doped polypyrrole, preparing a cross-linking agent, preparing conductive fibers, preparing modified polyacrylonitrile fibers, spinning and preparing the carpet. The preparation method comprises the following steps: adding modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a cross-linking agent into dimethylformamide, cross-linking at 170-190 DEG C for 30-50 minutes, then vacuumizing and defoaming at 45-55 DEG C to prepare a spinning solution, and preparing conductive fibers by adopting a wet spinning process; the anti-static carpet is good in anti-static effect and resistant to washing, and after the anti-static carpet is washed for 50 times, the voltage value is 2.66-2.75 kV and lower than 3 kV in a test method for evaluating the static performance of the carpet and simulating human walking, and the anti-static carpet meets the anti-static requirement of carpets in general places.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of carpets, and in particular relates to a method for preparing an antistatic carpet. Background Art

[0002] Static electricity is a ubiquitous physical phenomenon that has both wide application value and certain negative effects. In the field of carpets, when static electricity exists in carpets, it will bring a variety of negative effects, including: 1. Walking on the carpet may feel an electric shock, causing discomfort and fright; 2. Static electricity discharge may cause fire and explosion; 3. Static electricity will absorb dust and bacteria in the air. These harmful substances are more likely to accumulate on the surface of the carpet under the action of static electricity, causing effects on human health; 4. Static electricity on carpets may also interfere with the normal operation of electronic equipment.

[0003] Acrylic carpets have the advantages of moderate price, good warmth retention, softness, comfort, and easy cleaning. They have broad application prospects in commercial and residential areas. However, acrylic carpets have relatively poor electrical conductivity and weak ability to bind electrons. When acrylic carpets rub against other objects (such as soles, furniture, etc.), electrons are easily transferred between fibers, leading to the accumulation of charge and the generation of static electricity.

[0004] The copolymerization method for preparing antistatic acrylic fiber is to add comonomers (ethylene monomers containing hydrophilic groups such as hydroxyl, ether, carboxyl, and amide groups) during the polymerization of monomers to increase the hygroscopicity of acrylic fibers, thereby achieving an antistatic effect. The acrylic fibers prepared by this method have a comfortable feel, good flexibility, and are resistant to washing, but the antistatic effect is poor in a dry environment.

[0005] The conductive method refers to co-spinning acrylic fiber with conductive fiber. The resulting acrylic carpet can conduct the generated charge away, thereby achieving an anti-static effect. This method is not affected by environmental humidity, but conductive fibers are mostly dark in color, not easy to dye, and have poor color fastness, which has a greater impact on the appearance of the product. Conductive fibers have poor flexibility and are easy to break, so they are not resistant to washing.

[0006] Patent CN117646289B discloses an antifouling and antibacterial textile fabric and a preparation method thereof. In this technical solution, polyacrylonitrile fiber is prepared by uniformly mixing functionalized acrylonitrile copolymer, functionalized polypyrrole nanoparticles, 1,3-malondialdehyde, trifluoroacetic acid and dimethyl sulfoxide and wet spinning. Polypyrrole is a conductive polymer material that can form a conductive path inside the antifouling and antibacterial textile fabric, thereby giving the antifouling and antibacterial textile fabric good antistatic properties. However, polypyrrole is a black solid that has a great influence on the appearance of the fabric. The flexibility of polypyrrole is relatively poor, resulting in a poor feel of the fabric. In addition, during washing and friction, the polypyrrole will break, affecting the antistatic properties. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a method for preparing an antistatic carpet to achieve the following invention objectives: good antistatic effect, washing resistance, still meeting the antistatic standard after washing 50 times, good flexibility, high elongation at break, conductive fibers do not affect the appearance color of the carpet, and high color fastness to friction.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: A method for preparing an antistatic carpet comprises the following steps: 1. Preparation of modified polyacrylonitrile Add polyacrylonitrile to NaOH solution, stir and react at 60-80°C in a water bath for 1.5-2.5h, cool to room temperature, filter, wash the filter cake with ethanol and deionized water until neutral, and then dry in a drying oven at 50-70°C for 10-14h to obtain modified polyacrylonitrile; The degree of polymerization of the polyacrylonitrile is 1900 to 2100; The mass fraction of the NaOH solution is 10-20%; The stirring rate is 70-90 r / min.

[0009] 2. Preparation of 1-hydroxypyrrole doped polypyrrole Pyrrole is added to anhydrous CaCl2, shaken vigorously for 8 to 12 minutes, and then allowed to stand for 5 to 7 hours. Zinc powder and zeolite are then added, and vacuum distillation is performed. The fraction at 125 to 130°C is collected to obtain pretreated pyrrole. The pretreated pyrrole and 1-hydroxypyrrole were added to deionized water, mixed evenly, and then the FeCl3 solution was slowly added dropwise. After stirring and reacting for 22 to 26 hours in an ice water bath, the mixture was filtered, and the filter cake was washed with deionized water and ethanol alternately for 2 to 4 times, and then dried in a drying oven at 55 to 65° C. for 9 to 11 hours to obtain 1-hydroxypyrrole-doped polypyrrole; The mass ratio of pyrrole, anhydrous CaCl2, zinc powder and zeolite is 12-14:1-3:0.6-0.7:0.4-0.6; The mass ratio of the pretreated pyrrole, 1-hydroxypyrrole, deionized water, and FeCl3 solution is 1.5-2.5: 0.08-0.12: 280-320: 0.21-0.26; The time of adding FeCl3 solution dropwise is 25 to 35 minutes; The stirring rate is 40 to 60 r / min; The mass fraction of the FeCl3 solution is 4.4-4.9%.

[0010] 3. Preparation of cross-linking agent Cyclohexane hexanol and gluconic acid are added to deionized water, and then zinc acetate catalyst is added, and the mixture is heated to 110-150°C, steam is collected, and the steam is introduced into a saturated Na2CO3 solution. After cooling and stratification, the upper layer is collected to obtain the esterification product of cyclohexane hexanol and gluconic acid, i.e., a cross-linking agent; The mass ratio of the cyclohexanehexol, gluconic acid, deionized water and zinc acetate is 14-16:97-99:140-160:2-4.

[0011] 4. Preparation of conductive fibers Modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a crosslinking agent are added to dimethylamide, crosslinked at 170-190°C for 30-50 minutes, then vacuumed and defoamed at 45-55°C to prepare a spinning solution, and a conductive fiber is obtained by a wet spinning process; The mass ratio of the modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole, crosslinking agent and dimethylamide is 17-19: 0.8-1.2: 0.06-0.08: 95-105.

[0012] 5. Preparation of modified polyacrylonitrile fiber The modified polyacrylonitrile is added into dimethylamide, and vacuum defoamed at 45-55°C to prepare a spinning solution, and the modified polyacrylonitrile fiber is prepared by a wet spinning process. The mass ratio of the modified polyacrylonitrile to dimethylamide is 0.8-1.2:4.5-5.5.

[0013] 6. Spinning and making carpets The conductive fiber and modified polyacrylonitrile fiber are spun into yarn, and the yarn is connected to a carpet loom to obtain an antistatic carpet.

[0014] The yarns, each yarn comprising 6 to 8 modified polyacrylonitrile fibers and 1 to 3 conductive fibers; The antistatic carpet has a warp density of 160 to 200 strands / cm, a weft density of 350 to 450 strands / cm, and a pile height of 12 to 16 mm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. In the process of preparing the conductive fiber of the present invention, the hydroxyl group in 1-hydroxypyrrole-doped polypyrrole is connected to the side chain of modified polyacrylonitrile through an esterification reaction. Therefore, 1-hydroxypyrrole-doped polypyrrole has little effect on the flexibility of the main chain, and the elongation at break of the final antistatic carpet is 57-60%.

[0016] 2. In the process of preparing the conductive fiber of the present invention, the modified polyacrylonitrile is in a ring shape and densely wraps the modified polyacrylonitrile containing 1-hydroxypyrrole-doped polypyrrole in the side chain. Therefore, 1-hydroxypyrrole-doped polypyrrole has no effect on the color appearance of the antistatic carpet of the present invention, and the friction color fastness reaches level five, and the antistatic effect is good. In the carpet electrostatic performance evaluation simulated human walking test method, the voltage value before washing is 2.15-2.27 kV, and the voltage value after washing 50 times is 2.66-2.75 kV, both of which are lower than 3 kV, meeting the antistatic requirements of carpets in general places. DETAILED DESCRIPTION

[0017] Example 1 1. Preparation of modified polyacrylonitrile Add polyacrylonitrile to NaOH solution, stir and react at 70°C in a water bath for 2 hours, cool to room temperature, filter, wash the filter cake with ethanol and deionized water until neutral, and then dry in a drying oven at 60°C for 12 hours to obtain modified polyacrylonitrile; The degree of polymerization of the polyacrylonitrile is 2000; The mass fraction of the NaOH solution is 15%; The stirring rate is 80 r / min.

[0018] 2. Preparation of 1-hydroxypyrrole doped polypyrrole Pyrrole was added to anhydrous CaCl2, shaken vigorously for 10 minutes, and then allowed to stand for 6 hours. Zinc powder and zeolite were then added, and vacuum distillation was performed. The fraction at 128°C was collected to obtain pretreated pyrrole. The pretreated pyrrole and 1-hydroxypyrrole were added to deionized water and mixed evenly, and then the FeCl3 solution was slowly added dropwise, and the mixture was stirred and reacted for 24 hours in an ice-water bath, and then filtered. The filter cake was washed with deionized water and ethanol alternately for 3 times, and then dried in a drying oven at 60°C for 10 hours to obtain 1-hydroxypyrrole-doped polypyrrole; The mass ratio of pyrrole, anhydrous CaCl2, zinc powder and zeolite is 13:2:0.7:0.5; The mass ratio of the pretreated pyrrole, 1-hydroxypyrrole, deionized water, and FeCl3 solution is 2:0.1:300:0.24; The time for adding FeCl3 solution dropwise is 30min; The stirring rate is 50r / min; The mass fraction of the FeCl3 solution is 4.7%.

[0019] 3. Preparation of cross-linking agent Cyclohexane hexanol and gluconic acid are added to deionized water, and then zinc acetate catalyst is added, and the mixture is heated to 130°C, steam is collected, and the steam is introduced into a saturated Na2CO3 solution. After cooling and stratification, the upper layer is collected to obtain the esterification product of cyclohexane hexanol and gluconic acid, i.e., the cross-linking agent; The mass ratio of the cyclohexanehexol, gluconic acid, deionized water and zinc acetate is 15:98:150:3.

[0020] 4. Preparation of conductive fibers Modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a crosslinking agent are added to dimethylamide, crosslinked at 180°C for 40 minutes, then vacuumed and defoamed at 50°C to prepare a spinning solution, and a conductive fiber is prepared by a wet spinning process. The mass ratio of the modified polyacrylonitrile, 1-hydroxypyrrole-doped polypyrrole, crosslinking agent and dimethylamide is 18:1:0.07:100.

[0021] 5. Preparation of modified polyacrylonitrile fiber Modified polyacrylonitrile is added into dimethylamide, vacuumed and defoamed at 50°C to prepare a spinning solution, and modified polyacrylonitrile fiber is prepared by wet spinning process. The mass ratio of the modified polyacrylonitrile to dimethylamide is 1:5.

[0022] 6. Spinning and making carpets The conductive fiber and modified polyacrylonitrile fiber are spun into yarn, and the yarn is connected to a carpet loom to obtain an antistatic carpet.

[0023] The yarns, each yarn comprising 7 modified polyacrylonitrile fibers and 2 conductive fibers; The antistatic carpet has a warp density of 180 strands / cm, a weft density of 400 strands / cm, and a pile height of 14 mm.

[0024] Example 2 1. Preparation of modified polyacrylonitrile Add polyacrylonitrile to NaOH solution, stir and react at 60°C in a water bath for 1.5 hours, cool to room temperature, filter, wash the filter cake with ethanol and deionized water until neutral, and then dry in a drying oven at 50°C for 10 hours to obtain modified polyacrylonitrile; The degree of polymerization of the polyacrylonitrile is 1900; The mass fraction of the NaOH solution is 10%; The stirring rate is 70 r / min.

[0025] 2. Preparation of 1-hydroxypyrrole doped polypyrrole Pyrrole was added to anhydrous CaCl2, shaken vigorously for 8 minutes, and then allowed to stand for 5 hours. Zinc powder and zeolite were then added, and vacuum distillation was performed. The fraction at 125°C was collected to obtain pretreated pyrrole. The pretreated pyrrole and 1-hydroxypyrrole were added to deionized water and mixed evenly, and then the FeCl3 solution was slowly added dropwise, and the mixture was stirred in an ice-water bath for 22 hours, and then filtered. The filter cake was washed with deionized water and ethanol alternately for 2 times, and then dried in a drying oven at 55°C for 9 hours to obtain 1-hydroxypyrrole-doped polypyrrole; The mass ratio of pyrrole, anhydrous CaCl2, zinc powder and zeolite is 12:1:0.6:0.4; The mass ratio of the pretreated pyrrole, 1-hydroxypyrrole, deionized water, and FeCl3 solution is 1.5:0.08:280:0.21; The time for adding FeCl3 solution dropwise is 25min; The stirring rate is 40r / min; The mass fraction of the FeCl3 solution is 4.4%.

[0026] 3. Preparation of cross-linking agent Cyclohexane hexanol and gluconic acid are added to deionized water, and then zinc acetate catalyst is added, and the mixture is heated to 110°C, steam is collected, and the steam is introduced into a saturated Na2CO3 solution. After cooling and stratification, the upper layer is collected to obtain the esterification product of cyclohexane hexanol and gluconic acid, i.e., the cross-linking agent. The mass ratio of the cyclohexanehexol, gluconic acid, deionized water and zinc acetate is 14:97:140:2.

[0027] 4. Preparation of conductive fibers Modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a crosslinking agent are added to dimethylamide, crosslinked at 170°C for 30 minutes, then vacuumed and defoamed at 45°C to prepare a spinning solution, and a conductive fiber is prepared by a wet spinning process. The mass ratio of the modified polyacrylonitrile, 1-hydroxypyrrole-doped polypyrrole, crosslinking agent and dimethylamide is 17:0.8:0.06:95.

[0028] 5. Preparation of modified polyacrylonitrile fiber Modified polyacrylonitrile is added into dimethylamide, vacuumed and defoamed at 45°C to prepare a spinning solution, and modified polyacrylonitrile fiber is prepared by wet spinning process. The mass ratio of the modified polyacrylonitrile to dimethylamide is 0.8:4.5.

[0029] 6. Spinning and making carpets The conductive fiber and modified polyacrylonitrile fiber are spun into yarn, and the yarn is connected to a carpet loom to obtain an antistatic carpet.

[0030] The yarns, each yarn comprising 6 modified polyacrylonitrile fibers and 1 conductive fiber; The antistatic carpet has a warp density of 160 strands / cm, a weft density of 350 strands / cm, and a pile height of 12 mm.

[0031] Example 3 1. Preparation of modified polyacrylonitrile Add polyacrylonitrile to NaOH solution, stir and react at 80°C in a water bath for 2.5 hours, cool to room temperature, filter, wash the filter cake with ethanol and deionized water until neutral, and then dry in a drying oven at 70°C for 14 hours to obtain modified polyacrylonitrile; The degree of polymerization of the polyacrylonitrile is 2100; The mass fraction of the NaOH solution is 20%; The stirring rate is 90 r / min.

[0032] 2. Preparation of 1-hydroxypyrrole doped polypyrrole Pyrrole was added to anhydrous CaCl2, shaken vigorously for 12 minutes, and then allowed to stand for 7 hours. Zinc powder and zeolite were then added, and vacuum distillation was performed. The fraction at 130°C was collected to obtain pretreated pyrrole. The pretreated pyrrole and 1-hydroxypyrrole were added to deionized water and mixed evenly, and then the FeCl3 solution was slowly added dropwise, and the mixture was stirred and reacted for 26 hours in an ice-water bath, and then filtered. The filter cake was washed with deionized water and ethanol alternately for 4 times, and then dried in a drying oven at 65°C for 11 hours to obtain 1-hydroxypyrrole-doped polypyrrole; The mass ratio of pyrrole, anhydrous CaCl2, zinc powder and zeolite is 14:3:0.7:0.6; The mass ratio of the pretreated pyrrole, 1-hydroxypyrrole, deionized water, and FeCl3 solution is 2.5:0.12:320:0.26; The time for adding FeCl3 solution dropwise is 35min; The stirring rate is 60r / min; The mass fraction of the FeCl3 solution is 4.9%.

[0033] 3. Preparation of cross-linking agent Cyclohexane hexanol and gluconic acid are added to deionized water, and then zinc acetate catalyst is added, and the mixture is heated to 150°C, steam is collected, and the steam is introduced into a saturated Na2CO3 solution. After cooling and stratification, the upper layer is collected to obtain the esterification product of cyclohexane hexanol and gluconic acid, i.e., a cross-linking agent. The mass ratio of the cyclohexanehexol, gluconic acid, deionized water and zinc acetate is 16:99:160:4.

[0034] 4. Preparation of conductive fibers Modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a crosslinking agent are added to dimethylamide, crosslinked at 190°C for 50 minutes, then vacuumed and defoamed at 55°C to prepare a spinning solution, and a conductive fiber is prepared by a wet spinning process. The mass ratio of the modified polyacrylonitrile, 1-hydroxypyrrole-doped polypyrrole, crosslinking agent and dimethylamide is 19:1.2:0.08:105.

[0035] 5. Preparation of modified polyacrylonitrile fiber Modified polyacrylonitrile is added into dimethylamide, vacuumed and defoamed at 55°C to prepare a spinning solution, and modified polyacrylonitrile fiber is prepared by wet spinning process. The mass ratio of the modified polyacrylonitrile to dimethylamide is 1.2:5.5.

[0036] 6. Spinning and making carpets The conductive fiber and modified polyacrylonitrile fiber are spun into yarn, and the yarn is connected to a carpet loom to obtain an antistatic carpet.

[0037] The yarns, each yarn comprising 8 modified polyacrylonitrile fibers and 3 conductive fibers; The antistatic carpet has a warp density of 200 strands / cm, a weft density of 450 strands / cm, and a pile height of 16 mm.

[0038] Comparative Example 1 On the basis of Example 1, the preparation of 1-hydroxypyrrole doped polypyrrole in step 4 was changed to the preparation of polypyrrole, the addition of 1-hydroxypyrrole was omitted, the 1-hydroxypyrrole doped polypyrrole in step 6 was changed to polypyrrole, and the remaining steps were the same.

[0039] Comparative Example 2 On the basis of Example 1, the preparation of the cross-linking agent in step 5 is omitted, the addition of the cross-linking agent in step 6 is omitted, and the remaining steps are the same.

[0040] Test Example 1 The antistatic carpets prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were washed 50 times respectively according to GB / T17596-1998, and then the maximum voltage value of the antistatic carpet within 30 seconds before and after washing was tested according to GB / T18044-2000. The test results are shown in Table 1.

[0041] Table 1

[0042] Test Example 2 The color fastness to rubbing of the antistatic carpets prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was tested according to GB / T14252-2008, and the elongation at break of the antistatic carpets was tested according to GB / T 3923.1-1997. The test results are shown in Table 2.

[0043] Table 2

[0044] From the above results, we can see that: The antistatic carpet of the present invention comprises a conductive fiber prepared by wrapping 1-hydroxypyrrole-doped polypyrrole with a crosslinking agent through modified polyacrylonitrile; the side chain of the modified polyacrylonitrile contains a plurality of carboxyl groups, and the hydroxyl groups in the 1-hydroxypyrrole-doped polypyrrole are connected to the side chain of the modified polyacrylonitrile through an esterification reaction, so that the 1-hydroxypyrrole-doped polypyrrole has little effect on the flexibility of the main chain, and the final antistatic carpet has an elongation at break of 57-60%; Compared with Comparative Example 1, since Comparative Example 1 uses polypyrrole instead of 1-hydroxypyrrole to dope polypyrrole, in the prepared conductive fiber, polypyrrole and polyacrylonitrile main chain are mixed and spun, and polypyrrole has poor flexibility, which eventually leads to the breakage of polypyrrole in the conductive fiber of the antistatic carpet during the washing process. After washing 50 times, the voltage value is higher than 3kV, and the antistatic effect is poor; the elongation at break is low; The cross-linking agent prepared by the invention is a cyclic polyhydroxy structure. In the process of preparing the conductive fiber, the modified polyacrylonitrile is excessive. Under the action of the cross-linking agent, the modified polyacrylonitrile is cyclic and densely wraps the modified polyacrylonitrile containing 1-hydroxypyrrole doped polypyrrole in the side chain. Therefore, the 1-hydroxypyrrole doped polypyrrole has no effect on the appearance of the antistatic carpet of the invention. The friction color fastness reaches level five and the antistatic effect is good. In the carpet electrostatic performance evaluation method simulating human walking test, the voltage value before washing is 2.15-2.27 kV, and the voltage value after washing 50 times is 2.66-2.75 kV, both of which are lower than 3 kV, meeting the antistatic requirements of carpets in general places. Compared with Comparative Example 2, since no cross-linking agent was added when preparing the conductive fiber in Comparative Example 2, the polyacrylonitrile has a poor wrapping effect on the 1-hydroxypyrrole-doped polypyrrole, resulting in the exposure and breakage of the 1-hydroxypyrrole-doped polypyrrole in the conductive fiber during the washing or friction process of the antistatic carpet. The voltage value is higher than 3 kV after washing 50 times, and the antistatic effect is poor; the color fastness to friction is low.

Claims

1. A method for preparing an antistatic carpet, characterized in that: The preparation method comprises preparing modified polyacrylonitrile, preparing 1-hydroxypyrrole doped polypyrrole, preparing a cross-linking agent, preparing conductive fibers, preparing modified polyacrylonitrile fibers, spinning and making a blanket; The method for preparing 1-hydroxypyrrole doped polypyrrole comprises: adding pyrrole to anhydrous CaCl2, shaking for 8 to 12 minutes, standing for 5 to 7 hours, then adding zinc powder and zeolite, performing vacuum distillation, collecting a fraction at 125 to 130° C. to obtain pretreated pyrrole, adding the pretreated pyrrole and 1-hydroxypyrrole to deionized water, then slowly dropping a FeCl3 solution, stirring and reacting in an ice-water bath for 22 to 26 hours, filtering, washing the filter cake with deionized water and ethanol alternately for 2 to 4 times, and drying to obtain 1-hydroxypyrrole doped polypyrrole; The method for preparing the cross-linking agent comprises: adding cyclohexane hexanol and gluconic acid into deionized water, then adding a catalyst zinc acetate, heating to 110-150° C., collecting steam, introducing the steam into a saturated Na2CO3 solution, cooling and stratifying, collecting the upper layer material, and obtaining an esterification product of cyclohexane hexanol and gluconic acid, namely the cross-linking agent; The method for preparing the conductive fiber comprises adding modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole and a crosslinking agent into dimethylamide, crosslinking for 30 to 50 minutes at 170 to 190° C., vacuuming and defoaming at 45 to 55° C., preparing a spinning solution, and adopting a wet spinning process to prepare the conductive fiber.

2. The method for preparing an antistatic carpet according to claim 1, characterized in that: In the method for preparing 1-hydroxypyrrole doped polypyrrole, the mass ratio of pyrrole, anhydrous CaCl2, zinc powder and zeolite is 12-14: 1-3: 0.6-0.7: 0.4-0.6; the mass ratio of pretreated pyrrole, 1-hydroxypyrrole, deionized water and FeCl3 solution is 1.5-2.5: 0.08-0.12: 280-320: 0.21-0.26; the time for dripping FeCl3 solution is 25-35 minutes; the stirring rate is 40-60 r / min; and the mass fraction of FeCl3 solution is 4.4-4.9%.

3. The method for preparing an antistatic carpet according to claim 1, characterized in that: In the method for preparing the cross-linking agent, the mass ratio of cyclohexanehexol, gluconic acid, deionized water and zinc acetate is 14-16:97-99:140-160:2-4.

4. The method for preparing an antistatic carpet according to claim 1, characterized in that: In the method for preparing the conductive fiber, the mass ratio of modified polyacrylonitrile, 1-hydroxypyrrole doped polypyrrole, crosslinking agent and dimethylamide is 17-19: 0.8-1.2: 0.06-0.08: 95-105.

5. The method for preparing an antistatic carpet according to claim 1, characterized in that: The method for preparing modified polyacrylonitrile is to add polyacrylonitrile to a NaOH solution with a mass fraction of 10 to 20%, stir and react for 1.5 to 2.5 hours in a water bath at 60 to 80° C., cool, filter, wash with ethanol and deionized water, and dry to obtain modified polyacrylonitrile.

6. The method for preparing an antistatic carpet according to claim 1, characterized in that: The method for preparing modified polyacrylonitrile fiber is as follows: adding modified polyacrylonitrile with a mass ratio of 0.8-1.2:4.5-5.5 to dimethylamide, vacuuming and defoaming at 45-55° C., preparing a spinning solution, and adopting a wet spinning process to prepare the modified polyacrylonitrile fiber.

7. The method for preparing an antistatic carpet according to claim 1, characterized in that: The spinning and carpet making method comprises spinning the conductive fiber and the modified polyacrylonitrile fiber into yarn, and inserting the yarn into a carpet loom to obtain the antistatic carpet.

8. The method for preparing an antistatic carpet according to claim 7, characterized in that: In the spinning and carpet making method, each yarn contains 6 to 8 modified polyacrylonitrile fibers and 1 to 3 conductive fibers; the antistatic carpet has a warp density of 160 to 200 yarns / cm, a weft density of 350 to 450 yarns / cm, and a pile height of 12 to 16 mm.